Human Capital and Regional Budget Affect Economic Growth in East Nusa Tenggara Province - Radandima, Umbu Lakka Putra Pratama; Rumayya, Rumayya (Gorontalo Development Review, 2024)
This study aims to analyze how much influence human capital and government budget have on economic growth in districts / cities in East Nusa Tenggara Province in 2012-2021. This study uses secondary data sourced from the Central Bureau of Statistics and uses panel data regression analysis method with the selected method is Fixed Effect Model (FEM) in analyzing this research. The results show the influence of human capital (life expectancy and average years of schooling) and government budget on economic growth. while the expectation of years of schooling has no significant effect. This study provides recommendations to the government in improving the quality of the system and public services, especially in education and health, as well as the government in using the budget must be more efficient and targeted in using the budget so as to increase economic growth. Then from the academic side and the community to better know the importance of human capital and government budgets in increasing economic growth.